2010
DOI: 10.1016/j.mce.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between epidermal growth factor (EGF) receptor and extra nuclear steroid receptors in cell lines

Abstract: Please cite this article as: Migliaccio, A., Castoria, G., Giovannelli, P., Auricchio, F., cross talk between epidermal growth factor (egf) receptor and extranuclear steroid receptors in cell lines, Molecular and Cellular Endocrinology (2010), doi:10.1016/j.mce.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…DHTbound androgen receptor binds to the SRC SH3 domain, thereby releasing the kinase domain. SRC can then modulate ERK1/2 by phosphorylating SHC1 proteins to initiate the Ras-Raf-MEK-ERK pathway (24) or by phosphorylating EGFRs and increasing their ligand-induced activity (25). The experiments described herein suggest that DHT potentiates ERK1/2 signaling within 1 hour, leading us to hypothesize that androgens regulate ERK activation by a nontranscriptional mechanism.…”
mentioning
confidence: 70%
“…DHTbound androgen receptor binds to the SRC SH3 domain, thereby releasing the kinase domain. SRC can then modulate ERK1/2 by phosphorylating SHC1 proteins to initiate the Ras-Raf-MEK-ERK pathway (24) or by phosphorylating EGFRs and increasing their ligand-induced activity (25). The experiments described herein suggest that DHT potentiates ERK1/2 signaling within 1 hour, leading us to hypothesize that androgens regulate ERK activation by a nontranscriptional mechanism.…”
mentioning
confidence: 70%
“…Another model of this cross-talk has been proposed in which the ligand-activated EGFR phosphorylates ESR1 on tyrosine 537, thereby inducing ESR1-SRC association and kinase activation. SRC phosphorylates EGFR, which amplifies receptor activity and induces signal transduction activation (reviewed by Migliaccio et al 2010). PPT-induced ERK1/2 phosphorylation in the corpus of the epididymis was decreased by the EGFR kinase inhibitor, which indicates the involvement of ESR1-SRC-EGFR in the activation of ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…In hormone-responsive cells expressing both AR and ER (α and/or β), such as prostate and breast cancers, AR/ER/Src association plays a crucial role in activation of Src signals triggered by EGF and/or sex hormones (25,28). It was noteworthy that either AR or ER antagonist sufficiently inhibited this EGF-mediated association and subsequent stimulatory effects (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in prostate and breast cancers demonstrated that EGF induced AR/ER/Src association, resulting in activation of Src signaling (25,28) and that Src signals phosphorylated tyrosine residue of AR, provoking its transactivation and cell proliferation (29). We therefore investigated whether EGF induced AR/ER/ Src complex formation in UMUC3 which is ERα-negative/ ERβ-positive (figure not shown).…”
Section: Egf Induces Ar Association With Er and Srcmentioning
confidence: 97%
See 1 more Smart Citation